Sektor Unggulan Sebagai Penggerak Utama Penurunan Kemiskinan di Pacitan: - Mohammad Reihan; Wiwin Priana Primadhana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this research is to identify and classify the potential resources in Pacitan Regency so that can maximized optimally. This study employs a descriptive quantitative method, based on Gross Regional Domestic Product data at Constant Prices of 2010 for Pacitan Regency and East Java Province from 2018 to 2022. The analytical models used include Location Quotient, Shift Share, Typology Klassen, and followed by a 10-year poverty trend analysis. The results indicate that during this period, Pacitan Regency has only two leading sectors, suggesting the need for future efforts to balance the development of other sectors to avoid over-reliance on these leading sectors. This research serves as a reference for policy-making related to economic advancement in Pacitan Regency, ultimately contributing to poverty reduction.